RESPONS PERTUMBUHAN STUM MATA TIDUR KARET (Hevea brasiliensis Muell Arg.) DENGAN PEMBERIAN AIR KELAPA DAN PUPUK ORGANIK CAIR - Prihyanti Lasma E. Sinaga; Charloq Charloq; Nini Rahmawati (Jurnal Agroekoteknologi, 2013)
One of the problem encountered in rubber cultivation by rubber budded stump is high deathpercentage of stum in field. The research aim was to obtain useful rubber germ by cococut water soakand liquid organic fertilizer. The research was conduted at Kelurahan Pulo Brayan Bengkel Baru,Kecamatan East Medan (+ 25 meter above sea level) on June to October 2012.Completely randomized design with two factors and three replications. The first factor isthe duration coconut water soak (0, 12, 24 hour) and the second factor is liquid organic fertilizer(0, 20, 40, and 60 cc/plant). Parameters observated were percentage of break bud in field, time of brekbud, height of bud, diameter of bud, amount of leaf, root drived weight, shoot drived weight andpercentage of amount the death of stump at field. The result showed that period of coconut watersoak significantly affect the to percentage of broken bud 2 weeks after plant and the time of brek therubber bedded stump. The liquid organic fertilizer significantly affect to time of break stump, heightof bud, and shoot drived weight. Interaction of coconut water and liquid organic ferlilizer was notsignificantly effect to all paremeters. The best sit of coconut water is 12 hour and dose of liquidorganic fertilizer is 60 cc/plant.Key word : rubber budded stump, coconut water, liquid organic water, growth